Study on the Evaluation of Transmission Gear Rattle Noise based on Rigid-flexible Coupling Model - Xiaohui Shi; Wenxiang Dai; Dong Guo; Xiuwen Xiong; Jiao Liu (Jixie chuandong)
Taking into account factors such as input speed fluctuation， structural characteristics and gear meshing characteristics of the transmission， the flexible characteristics of the transmission box are considered， boundary conditions are properly set up， and transmission gear rattle rigid-flexible coupling simulation analysis models are established to reproduce the gear rattle. Then， refer to speed of idle gears， the effectiveness of the analysis model is verified by bench test. According to the gear rattle mechanism，gear rattle evaluation index based on the speed fluctuation vector sum of the driving and loose gears is proposed. Based on the validated simulation model， jerk and speed fluctuation vector sum evaluation indicators are calculated and analyzed under the gear rattle conditions， and comparing with the subjective evaluation results. The results show that the speed fluctuation vector sum of the driving and loose gears has good consistency with subjective evaluation result. It provides a methodological reference for the objective evaluation of gear rattle noise.